Effects of Alpine Wetland Landscapes on Regional Climate on the Zoige Plateau of China - Junhong Bai; Qiongqiong Lu; Qingqing Zhao; Junjing Wang; Hua Ouyang (Advances in Meteorology)
The differences in the air temperature, precipitation, evaporation, and relative humidity between wetlands and nonwetlands were analyzed to investigate the effects of alpine wetlands on regional climate. Meanwhile, the changes in precipitation and surface runoff fluxes before and after the typical wetland degradation were discussed, and the effects of wetland degradation on soil organic carbon were assessed. Correlation and regression analyses were applied to exhibit the relationships between wetland landscape areas and meteorological factors. Our results showed that the cooling effects of wetlands on ambient environment were very obvious, and soil temperature could be higher in the area with less surrounding wetland area. The evaporation capacity and relative humidity in wetlands were higher compared to the surrounding non-wetlands. Precipitation and surface runoff flux decreased due to serious wetland degradation, indicating that wetland degradation or expansion had close relation with regional precipitation. Once peat soils were converted to meadow soils or Aeolian sandy soils, soil organic carbon (SOC) would decline linearly. Correlation and regression analyses showed that there were significant correlations between wetland landscape areas and the annual average air temperature, the average air temperature in growing seasons, and the evaporation in growing seasons (P<0.05).